Maintaining Performance Under Pressure: The Role of Work-Life Balance, Burnout, and Psychological Well-Being - Fery Indah Kuswita; Eva Desembrianita; Muhammad Rosyihuddin (Fundamental and Applied Management Journal, 2026)
This study examines the effects of work-life balance and burnout on employee performance, with psychological well-being as a mediating variable. A quantitative survey was conducted involving 210 employees from various sectors characterized by high work demands. Respondents were selected using simple random sampling, and the data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings indicate that work-life balance positively and significantly influences psychological well-being and employee performance, whereas burnout negatively and significantly affects both variables. Psychological well-being also has a positive effect on employee performance. Mediation analysis revealed that psychological well-being significantly mediates the relationship between work-life balance and employee performance (indirect effect = 0.259, p = 0.001) as well as the relationship between burnout and employee performance (indirect effect = −0.203, p = 0.003). These results suggest that psychological well-being serves as an important mechanism through which work-life balance enhances performance and burnout diminishes performance. This study contributes to the literature by providing empirical evidence on the mediating role of psychological well-being in explaining employee performance within high-pressure work environments.